Library Users’ Intention to Continue Using USULib Mobile Post the COVID-19 Pandemic - Himma Dewiyana; Darmayana, Dean Muhammad (Program Studi Ilmu Perpustakaan UIN Alauddin, 2023)
The use of mobile phones has increased in various areas during the COVID-19 pandemic, including the adoption of mobile libraries. This research aims to understand users' intentions to continue using USULib Mobile after the pandemic. Using a quantitative descriptive approach, the study focused on the entire population of USU Library users who utilize USULib Mobile, with a research sample of 250 respondents. Data collection involved questionnaires, observations, and documentation studies covering eight UTAUT2 indicators, twenty-six variables, and forty-six questions. Descriptive methods were used for data analysis, and data validity was assessed using a rating scale. The results showed a generally strong inclination among users to persist in using USULib Mobile after the COVID-19 pandemic. The most influential factor was habit, particularly linked to the experience variable, indicating that the use of USULib Mobile had become a deeply ingrained habit during the pandemic. On the contrary, the least influential factor was hedonic motivation, specifically the variable related to fun or pleasure, which requires further investigation.